Impact of prior arthroscopic rotator cuff repair on postoperative outcomes of reverse shoulder arthroplasty: a comparative analysis of muscle strength recovery and clinical results - Yoshihiro Hirakawa, MD, PhD; Tomoya Manaka, MD, PhD; Katsumasa Nakazawa, MD, PhD; Yoichi Ito, MD, PhD; So Taniguchi, MD; Ayako Ogura, PT; Hidetomi Terai, MD, PhD (JSES International, 2025)
Background: Although the postoperative outcomes of reverse total shoulder arthroplasty (rTSA) are favorable, few studies have examined the impact of previous arthroscopic rotator cuff repair (ARCR) on rTSA outcomes in detail. This study aimed to evaluate and compare the short-term outcomes of rTSA in patients without previous ARCR (control group) and those with a history of ARCR (previous ARCR group). By focusing on postoperative range of motion, clinical scores, and muscle strength over a minimum 2-year follow-up period, we sought to reveal critical insights into how previous ARCR influences recovery trajectories. Methods: We analyzed all patients diagnosed with cuff tear arthropathy or massive rotator cuff tears who underwent rTSA between April 2014 and March 2021, with at least two years of follow-up. The follow-up rate was 81.4% (228/280). The exclusion criteria included revision arthroplasty, infection, previous open surgery, and additional tendon transfer. The key metrics assessed were range of motion, American Shoulder and Elbow Surgeons (ASES) score, Constant score (CS), visual analog scale score for pain, and muscle strength. Results: In total, 228 patients were included: 182 (mean age: 76 years) in the control group and 46 (mean age: 75 years) in the previous ARCR group. Active elevation improved significantly from 77° to 121° in the control group and from 81° to 116° in the previous ARCR group. External rotation at the side showed no significant change in either group, whereas internal rotation worsened postoperatively in both groups. The ASES, CS, and visual analog scale scores showed significant improvements 2 years postoperatively in both groups. However, the control group had significantly higher postoperative ASES and CS scores than those in the previous ARCR group. Muscle strength significantly improved in the control group but not in the previous ARCR group. Conclusion: Postoperative muscle strength improvement was not observed in patients undergoing rTSA with a history of ARCR, and their postoperative clinical outcomes were inferior to those undergoing rTSA without a history of ARCR. This deficiency in muscle strength improvement may contribute to the differences in clinical scores, a factor that surgeons need to consider.